Methods for Controlling Woody Invasian into CRP Fields in Tennessee - John P. Gruchy; Craig A. Harper; Matthew J. Gray (National Quail Symposium Proceedings, 2017)
Woody cover is an important component of northern bobwhite (Colinus virginianus) habitat; however, some species such as red maple (Acer rubrum) and sweetgum (Liquidambar styraciflua) grow aggressively and may become dominant on unmanaged areas. Six treatments with controls were implemented in a completely randomized design on a Conservation Reserve Program (CRP) old-field planted to tall fescue (Lolium arundinarium) with extensive invasion by sweetgum, red maple, and other woody saplings to determine the most effective method for reducing coverage of woody plants. Treatments included dormant-season burning in March 2004, applications of triclopyr, imazapyr, and glyphosate in July 2004, mowing in August 2004, and growing-season burning in September 2004. Resulting vegetation structure and composition were measured in July 2005. Percentage woody cover was reduced by all treatments (13-50%) except mowing (65.8%, SE=7.0) compared to control (80.4%, SE=7.6). Imazapyr (13.3%, SE=2.6), growing-season burn (14.2%, SE=3.1), and triclopyr (15.8%, SE=3.5) were most effective at reducing woody cover. Percentage cover of desirable legumes (Chamaecrista spp., Desmodium spp., Lespedeza spp.) was greatest in growing-season burn (54.2%, SE=6.7), imazapyr (28.3%, SE=5.9), and dormant-season burn (24.5%, SE=5.2) treatments. Imazapyr increased coverage of blackberry (Rubus spp.), while triclopyr increased coverage of warm- and cool-season grasses. Our results suggest growing-season fire in September was best at reducing woody plants and enhancing habitat for northern bobwhites. Growing-season fire resulted in the greatest coverage of desirable legumes, reduced litter depth, and increased percent bare ground. If burning is not possible, applications of imazapyr or tryclopyr may be suitable alternatives.
Keywords: Colinus virginianus; fire; herbicide; northern bobwhite; September burn; sweetgum; woody control